2010
DOI: 10.1111/j.1365-2796.2009.02197.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for end‐stage renal disease in a community‐based population: 26‐year follow‐up of 25 821 men and women in eastern Finland

Abstract: Abstract. Kastarinen M, Juutilainen A, Kastarinen H, Salomaa V, Karhapää P, Tuomilehto J, Grönhagen-Riska C, Jousilahti P, Finne P. (Kuopio University Hospital, Kuopio; National Institute for Health and Welfare, Helsinki; University of Helsinki, Helsinki; South Ostrobotnia Central Hospital, Seinäjoki; Finnish Registry for Kidney Diseases, Helsinki; Helsinki University Central Hospital, Helsinki; and University of Tampere, Tampere; Finland). Risk factors for endstage renal disease in a community-based populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 49 publications
2
30
1
2
Order By: Relevance
“…The loss of association between obesity measures and incident CKDs3-5 after risk factor adjustment suggest that the relation between obesity and CKDS3-S5 may be attributed to the presence of diabetes or hypertension. In 26 year follow-up in Eastern Finland, the independent effect of obesity on ESRD risk seemed to appear only just before the end of study [28]; hence, the lack of independent risk of obesity in our study might be related to the medium duration of follow-up. Interestingly, among men higher WC was associated with a lower risk for incident CKDs3-5 which was marginally significant [0.703(0.476–1.040), P = 0.078]; a similar finding among the male population of Hoorn study was shown,applying change in renal function as the incident CKD rather than using a predefined threshold [9].It could be speculated that lower risk of incident CKD among TLGS population with abdominal adiposity might be attributable to healthier life because of increased awareness among cohort population however, we recently [29] demonstrated that there is increasing trend in the prevalence of general and abdominal obesity among TLGS participants during phase 2 and 3 in both genders.…”
Section: Discussioncontrasting
confidence: 49%
“…The loss of association between obesity measures and incident CKDs3-5 after risk factor adjustment suggest that the relation between obesity and CKDS3-S5 may be attributed to the presence of diabetes or hypertension. In 26 year follow-up in Eastern Finland, the independent effect of obesity on ESRD risk seemed to appear only just before the end of study [28]; hence, the lack of independent risk of obesity in our study might be related to the medium duration of follow-up. Interestingly, among men higher WC was associated with a lower risk for incident CKDs3-5 which was marginally significant [0.703(0.476–1.040), P = 0.078]; a similar finding among the male population of Hoorn study was shown,applying change in renal function as the incident CKD rather than using a predefined threshold [9].It could be speculated that lower risk of incident CKD among TLGS population with abdominal adiposity might be attributable to healthier life because of increased awareness among cohort population however, we recently [29] demonstrated that there is increasing trend in the prevalence of general and abdominal obesity among TLGS participants during phase 2 and 3 in both genders.…”
Section: Discussioncontrasting
confidence: 49%
“…Furthermore, a mildly reduced GFR (60-90 mL/min/1.73 m 2 ) predicted the progression to kidney disease. Based on a Finnish study, diabetes mellitus, hypertension, obesity, and male gender were independent risk factors for ESRD in the general population [31]. Kronborg et al [32] studied factors that predicted a change in eGFR during a 7-year follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Beside gender differences in physiological factors the lower prevalence may also be a function of the correction factor for females in the Cr-based equations. Men are de facto also at higher risk for ESRD compared to women, which is also indirect evidence for a higher burden of the underlying CKD, which finally may progress to ESRD [18]. …”
Section: Discussionmentioning
confidence: 99%